2018
DOI: 10.1093/nar/gky1107
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing reveals two populations of damage-induced small RNAs at endogenous DNA double-strand breaks

Abstract: Recent studies suggest that transcription takes place at DNA double-strand breaks (DSBs), that transcripts at DSBs are processed by Drosha and Dicer into damage-induced small RNAs (diRNAs), and that diRNAs are required for DNA repair. However, diRNAs have been mostly detected in reporter constructs or repetitive sequences, and their existence at endogenous loci has been questioned by recent reports. Using the homing endonuclease I-PpoI, we have investigated diRNA production in genetically unperturbed human and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 52 publications
3
78
0
Order By: Relevance
“…We used an inducible Drosha knock-out cell line to validate the miRNA dependence of these covariances (Methods), and sequenced the transcriptomes of 343 of these knock-out cells using clonal expansion from a single cell and sorting of cells in G2/M phase as described above. We have previously demonstrated the global loss of miRNAs in this particular cell line 34 . As expected, there is no covariance enrichment in miRNA target sets in Drosha knock-out cells (Figure 2B), demonstrating that these covariances are directly caused by miRNA activity.…”
Section: Resultsmentioning
confidence: 79%
“…We used an inducible Drosha knock-out cell line to validate the miRNA dependence of these covariances (Methods), and sequenced the transcriptomes of 343 of these knock-out cells using clonal expansion from a single cell and sorting of cells in G2/M phase as described above. We have previously demonstrated the global loss of miRNAs in this particular cell line 34 . As expected, there is no covariance enrichment in miRNA target sets in Drosha knock-out cells (Figure 2B), demonstrating that these covariances are directly caused by miRNA activity.…”
Section: Resultsmentioning
confidence: 79%
“…We speculate that the presence of a GC-rich sequence downstream of the TOP motif in RP genes (Meyuhas and Kahan, 2015) may explain in part why R-loops formed at RPG loci are stable and capable of reducing the rate of transcription, unless they are actively destabilized by the Ddx5 helicase. It has been reported that the Microprocessor complex is recruited to DNA double strand break (DSB) sites, where it facilitates R-loop formation and promotes DSB repair (Bonath et al, 2018;Crossley et al, 2019;Lu et al, 2018). Thus, the Microprocessor may participate in both the formation and the resolution of R-loops, depending on the cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19–23 ] DilncRNAs were identified using strand specific RT‐qPCR (ssRT‐qPCR) and were postulated to be the precursors of damage‐induced small RNAs (diRNAs). [ 19,20,22,24 ] Production of dilncRNAs is sensitive to RNAPII inhibitors, but not to inhibitors specific to other RNA polymerases. Their RNAPII dependency has been further supported by the observation of a DSB‐dependent increase of RNAPII occupancy in a 4 kb window around break sites and a corresponding increase of transcripts mapping to sequences around the break.…”
Section: De Novo Rna Synthesis At Dsbs: An Unexpected Discoverymentioning
confidence: 99%